Analysis of Parents Interest in Enrolling Their Children at SDN 7 Pajo - Amin, M.; Ilyas, Ilyas (Fitrah, 2025)
Interest is the impulse or desire of an individual towards an object that attracts his attention. In the context of education, interest has an important role in the sustainability of the institution. Low interest can have an impact on the decline of the existence of these educational institutions. In general, interest can be influenced by two factors, namely internal factors that come from within the individual, and external factors that come from the outside environment. This study aims to analyze the level of public interest in sending children to school at SDN 7 Pajo. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. This approach is intended to explore in depth the factors that encourage people to choose SDN 7 Pajo Dompu Regency as the place of education for their children. Data is analyzed through the process of reduction, data presentation, and conclusion drawn. Data validity is strengthened through triangulation of sources, time, and techniques, as well as increased diligence in data collection. The results of the study show that public interest in sending children to SDN 7 Pajo is still at a moderate level. This is reflected in the fact that 50% of parents whose children graduated from Aisyiah Kindergarten choose to send their children to schools that have more and varied religious lessons, and have better quality standards and services, for example at SDIT Imam Buhari, MI Alkautsar, SDIT Hilmi, and SDN 20 Dompu. The factors that affect this interest consist of two groups, namely: 1) internal factors such as motivation and individual needs, and 2) external factors such as family environment, economy and quality of education.